2010
DOI: 10.2172/1000159
|View full text |Cite
|
Sign up to set email alerts
|

Identifying at-risk employees: A behavioral model for predicting potential insider threats

Abstract: SummaryA model was developed to assess employees' behavioral manifestations of a number of psychological and personality predispositions that are hypothesized to indicate an increased risk of insider abuse. This psychosocial model is based on case studies and research literature on factors and correlates associated with behavioral precursors of individuals committing insider crimes. In many of these crimes, managers and other coworkers observed that the offenders had exhibited signs of stress, disgruntlement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…The results from this research were consistent with results obtained by the authors' collaborators using a similar approach that utilized a proprietary dataset containing messages from a similar number of individuals [3][4]. The current research employed greater automation, a larger sample of text that was available in the public domain, and additional analysis to identify which word categories had the greatest influence on factor scores.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The results from this research were consistent with results obtained by the authors' collaborators using a similar approach that utilized a proprietary dataset containing messages from a similar number of individuals [3][4]. The current research employed greater automation, a larger sample of text that was available in the public domain, and additional analysis to identify which word categories had the greatest influence on factor scores.…”
Section: Discussionsupporting
confidence: 84%
“…This test did not produce the expected result as two of the known criminals actually used a relatively large number of agreeable words compared to the overall corpus. The authors' collaborators used a different approach in a separate study [3] and [4] analyzing messages for high frequencies of words negatively correlated with agreeableness. In that study, known criminals were found at the critical level for the agreeableness factor.…”
Section: Computational and Analytic Processmentioning
confidence: 99%
See 2 more Smart Citations
“…20 The indicators used in the model, such as disgruntlement, anger management issues, and disregard for authority, are shown in Figure 2. It is worth noting that these psychosocial indicators contribute differentially to the judged level of psychosocial risk, with disgruntlement, difficulty accepting feedback, anger management issues, disengagement, and disregard for authority having higher weights than other indicators, for example.…”
Section: Multiple Domains Of Datamentioning
confidence: 99%